Simplified flocculation model for inorganic and polymer flocculants - Kadooka, Hiroto; Miyajima, Takumi; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (Elsevier, 2017)
Simulation of the flocculation process using both inorganic and polymer flocculants is very difficult because there are many factors that influence the process. In this study, a model that enables the visual understanding of the qualitative trends of the flocculation system using both inorganic and polymer flocculants is proposed. It is a simplified one-dimensional model that expresses flocculation under various additive manners of the flocculant. Various kinds of thought experiments as well as experimental runs with model flocculants were carried out based on the model; the results demonstrate that the model can express many empirical qualitative trends of flocculation.